Space and Approach in "The Virtuous City": A Tale of Two Universities: Re-imagining and reconstruction of the westernised South African university (The Strategic Review for Southern Africa, 2021)
In order to know how to change one must be able to acknowledge what one does not know. Central to knowledge production of relevance is humility and an understanding of the realities of one’s own environment. From a decolonial perspective, knowledge production is affected by the development and creation of the actual physical spaces of the university and its pedagogy. The Covid_19 pandemic has tested the functionality of the physical space of the university as well as the organization of the city space.  This paper considers these issues, their impact and effect on the mental well-being of both academics and students by exploring the idea of the university as a virtuous city. We draw on Al-Farabi’s treatise of the Virtuous City because physical and conceptual architectures reflect a way in which the world is structured. In South Africa, the violent design of the fragmented spaces has been planned according to the colonial, cartographic imagination which destroys and distorts memory and ruptures tradition. The architecture of the cities and universities, it can be argued, effect a similar process, and serve as an affirmation of the pre-dominance of the white-supremacist power structure in South Africa.  Cities are created by people and each city is a creation of the interaction of social, economic, cultural, and political imperatives. The university is a micro-manifestation of the cosmopolitan city that adopts different approaches to knowledge, decolonisation and transformation. In re-imaging and reconstituting the westernised South African university an appropriate approach to reaching the ideals of well-being and harmony would require the shedding of the ego and the Cartesian “I”. The process of decolonising the university should occur by deconstructing and recognising colonial methods, theories and practise in our pedagogy and spaces in order to begin the process of reconstruction.
Keywords: decoloniality; deconstruction; reconstruction; mental illness; well being; virtuous city